Clinical significance of determining neutrophil extracellular traps in women with oncogynecological neoplasms - Z. D. Aslanova; J. Kh. Khizroeva; A. G. Solopova; V. A. Solodkiy; A. V. Vorobev; D. V. Blinov; M. D. Aslanova; I. A. Nakaidze; J.-C. Gris; I. Elalamy; A. D. Makatsariya (Акушерство, гинекология и репродукция, 2024)
The formation of neutrophil extracellular traps (NETs), described first in 2004 as a previously unknown neutrophil strategy for combating microbes, has been attracting a growing interest in research community. NETs play a key role in inflammation and infection exploiting effector functions such as degranulation, phagocytosis as well as production of reactive oxygen species (ROS). NETs play a crucial role in defense against systemic infections. Additionally NETs involved in inflammation, and in the pathogenesis of non-infectious diseases, such as autoimmune diseases and cancer.